Pengembangan Media KPKPD (Kartu Papan Kebutuhan Peserta Didik) Materi Aku dan Kebutuhanku pada IPAS Kelas IV SD Negeri 8 Pangkalanbaru - Selli Agustin; Feri Ardiansah; Hevitria (JBES (Journal Basic Education Skills), 2026)
This study is based on a needs analysis of students, which revealed that most students experienced difficulties in understanding the material when relying solely on textbooks. They showed higher motivation to learn through engaging visual media, particularly in the "Aku dan Kebutuhanku" topic. This research aims to develop KPKPD (Student Needs Board Cards) as an instructional medium that is valid, practical, and potentially effective for fourth-grade students at SD Negeri 8 Pangkalan Baru. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The subjects of the study were 35 students. Data collection instruments included needs analysis sheets, expert validation questionnaires, teacher and student response questionnaires, and tests. The data were analyzed using both qualitative and quantitative methods.The results of media expert validation indicated a score of 71.11%, categorized as highly valid. Validation by two material experts yielded scores of 97% and 80%, both falling within the high validity range. The average percentage of the pretest and posttest results reached 80%, indicating a high level of validity. Teacher and student response questionnaires from both small and large group trials showed 100%, demonstrating that the media is highly valid and practical. The normality test results showed that the data were normally distributed, with pretest and posttest values of 0.281 and 0.116, respectively. Furthermore, the hypothesis test produced a significance value of 0.000, indicating a significant difference before and after the implementation of the KPKPD (Student Needs Board Cards) media.